Case ReportA rare case of waxing and waning supraclavicular swelling due tointernal jugular vein saccular varix in a 79-year-old male with chronicobstructive pulmonary disease - Handa, Prince; Singh, Ishwar; Gopal, Ashish; Mylswamy, Sabareesh; Ahmad, Shafaat; Mangla, Anubha (Indian Journal of Case Reports, 2026)
Supraclavicular swellings encompass a broad range of infectious, neoplastic, and vascular etiologies. A 79-year-oldmale with a history of chronic smoking and chronic obstructive pulmonary disease presented with a right-sided neck mass that had progressed from the size of a pea to a lemon over 3 months. The swelling exhibited a unique “waxing and waning” pattern, appearing prominently during coughing and Valsalva maneuvers and resolving completely afterward. Clinical examination revealed a 3 × 3 cm soft, non-pulsatile cystic mass. Ultrasound and computed tomography angiography confirmed a focal saccular aneurysmal dilatation of the right internal jugular vein, measuring 3.2 cm in diameter. In the absence of complications, such as thrombosis or compressive symptoms, conservative management and regular follow-up are preferred over surgical intervention. This case emphasizes the importance of considering rare vascular anomalies in the differential diagnosis of dynamic neck masses.